2014
DOI: 10.1155/2014/932160
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Mesoporous Silica Wires with Intrawire Lamellae via Evaporation‐Induced Self‐Assembly in Space‐Confined Channels

Abstract: Evaporation-induced self-assembly (EISA) of silica sol-gel ethanol-water solution mixtures with block-copolymer were studied inside uniform micro/nano-channels. Nanostructured mesoporous silica wires, with various intrawire self-assembly structures including lamellae, were prepared via EISA process but in space-confined channels with the diameter ranging from 50 nm to 200 nm. Membranes made of anodized aluminum oxide (AAO) and track-etched polycarbonate (EPC) were utilized as the arrays of space-confined chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Zhang et al [60] found that it is necessary to add acetylacetone during the hydrolysis process because acetylacetone as a complexing agent can inhibit the hydrolysis rate of the titanium source, thus preventing the rapid formation of precipitates and favoring the formation of ordered mesoporous structures. Hu et al [61] used EISA method to improved sol-gel and obtained titanium dioxide samples. They found that the constant volatilization of solvents and inorganic acids also enhances the polycondensation between inorganic particles.…”
Section: Types Of Ordered Mesoporous Materialsmentioning
confidence: 99%
“…Zhang et al [60] found that it is necessary to add acetylacetone during the hydrolysis process because acetylacetone as a complexing agent can inhibit the hydrolysis rate of the titanium source, thus preventing the rapid formation of precipitates and favoring the formation of ordered mesoporous structures. Hu et al [61] used EISA method to improved sol-gel and obtained titanium dioxide samples. They found that the constant volatilization of solvents and inorganic acids also enhances the polycondensation between inorganic particles.…”
Section: Types Of Ordered Mesoporous Materialsmentioning
confidence: 99%
“…Porous AAO membranes are usually used as a template to prepare 1D polymer nanostructures because of the simple preparation method, low-cost, and high uniformity of the nanostructures. 15 17 Many methods can been used for preparing polymer nanowires and nanocables through the AAO template, such as electrodeposition, 18 , 19 self-assembled, 20 chemical vapor deposition, 21 photolithographic approaches, 22 layer-by-layer deposition, 23 , 24 and physical wetting. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Porous AAO membranes are usually used as a template to prepare 1D polymer nanostructures because of the simple preparation method, low-cost, and high uniformity of the nanostructures. 15−17 Many methods can been used for preparing polymer nanowires and nanocables through the AAO template, such as electrodeposition, 18,19 self-assembled, 20 chemical vapor deposition, 21 photolithographic approaches, 22 layer-by-layer deposition, 23,24 and physical wetting. 25 The rare earth (RE) complexes have been attractive materials because of their distinct and desired luminescence performances, for instance, low excitation energy, good monochromaticity, and long fluorescence lifetimes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, synthesis of mesoporous silica inside the columnar channels of an anodic alumina membrane (AAM) has been extensively studied, and 1D or 2D hexagonally ordered or stacked (circular) mesostructure has been fabricated inside the columnar AAM channels by using cationic, nonionic and block copolymer surfactants as template and structuralguided synthesis (Martin, 1994;Nishizawa et al, 1995;Wu et al, 2004a,b;Platschek et al, 2006;Hu et al, 2014). However, the extensive synthesis conditions might lead to very difficult control over the 3D channel geometry in the final replica along the entire AAM channels.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, recent progresses could be utilized to modify the synthesis protocols for more morphological control and better future applicability. Thus; fabrication of intrawire nanoporous structure with its lamellar disks perpendicular to the mesoporous silica wire axis (Hu et al, 2014), synthesis of silica nanotubes with orientation controlled mesopores (Zhang et al, 2012) and synthesis of polymers, metal oxides, and alloys magnetic nanoparticles coordinated with mesoporous silica membranes (Cauda et al, 2012 andAlamri et al, 2014) could be achieved.…”
Section: Introductionmentioning
confidence: 99%